Corinne Bisland: capstone - Bisland, Corinne, artist (Colorado State University. Libraries, 2015)
The artist's statement: My entire life has been guided by an artistic sensibility. From as early as I can remember, I always had some sort of artistic medium in my hands. Photography became my greatest passion when my whole world changed at 9 years old. I endured severe trauma to my body resulting in an incurable, chronic pain disorder called Reflex Sympathetic Dystrophy. This was when I began to see my world differently. I focused my energy into photography instead of my pain. I was able to find joy through this hard time in the discovery of the beauty of nature. This body of work emerges from a desire of a real sensory experience. I have gone back to my roots of finding the beauty in personal experiences. When I look at the world through a photographic eye I see objects illuminated, surfaces painted by the depth of light and shadows, and the unique textures of everything around us. Each image is paired with a poem describing what I feel, smell, and think in the space while experiencing life. These experiences and thoughts are uniquely my own, which is the root of my photographic passion. The five displayed works are archival ink prints, incased in handmade light boxes. The illumination of the images brings forth the details of the natural world. All elements included in an image are samples from a specific space, arranged to convey my personal emotion of the time. Overall, these displays are a little insight into my world and how I find happiness through the many obstacles in life.
Where life takes me
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.